Analisis Proses Produksi Bottom Satu Outsole di PT. XYZ - Mawarti Mawarti; Fatkhuri Fatkhuri (Lembaga Pengembangan Kinerja Dosen, 2026)
Tight competition in the footwear industry requires companies to carry out production processes effectively and efficiently. Good production management will have an impact on the quality of the products produced and the achievement of the company's production targets. The purpose of compiling this internship report is to study and analyze the shoe production process based on the operational management perspective at PT. XYZ. The benefits of the report discussed are as a direct means in the world of work and as evaluation material for the company. The FAJAR Internship Activity of the Sharia Business Management Study Program in 2025 was carried out at PT. XYZ in the production department. Data collection was carried out using several techniques, namely direct observation of the production process, interviews with related parties, and documentation during the implementation of the internship activities. Based on the results of the analysis carried out, the production process at PT. XYZ is divided into several stages, preparation of raw materials, cutting processes, pressing and trimming (hotpress), to quality control. The implementation of operational management has been quite successful with a clear division of tasks, but challenges remain, such as limited production time and coordination between departments. The conclusion of this internship report is that the implementation of operational management has supported the smooth running of production activities, although improvements are still needed. It is recommended that the company improve coordination between departments and conduct regular production process evaluations to improve process efficiency and product quality.